Pemberdayaan UMKM Pengrajin Kayu melalui Pelatihan Keselamatan dan Kesehatan Kerja (K3) di Mojowarno Kabupaten Jombang - Sudarso, Sudarso; Dzinnur, Cilda Thesisa Ilmawan; Ikhwanuddin, Ikhwanuddin; Saleh, Mochamad; Triono, Bambang; Anwar, Moh. Syaiful; Munir, Misbachul (Jurnal Pengabdian Masyarakat, 2025)
Woodcraft micro, small, and medium enterprises (MSMEs) face relatively high occupational risks due to the intensive use of machinery, sharp tools, and continuous exposure to wood dust and noise. Limited knowledge and weak implementation of Occupational Safety and Health (OSH) principles remain key factors contributing to the elevated risk of workplace accidents. This community service program aimed to improve knowledge, risk awareness, and safe work behavior among woodcraft workers in Mojowarno District, Jombang Regency. The study employed a descriptive qualitative approach using field observation, semi-structured interviews, pre-test and post-test, and activity documentation. The training was conducted on 17–20 September 2025 and involved ten woodcraft workers. The results indicated an improvement in participants’ understanding of the proper use of personal protective equipment (PPE), the application of safe work procedures, and better organization of the work environment.